The role of soils in environmental sorption and degradation processes of selected Fusarium mycotoxins - Sven Korz; Katherine Muñoz (Discover Soil)
Abstract Mycotoxins, toxic secondary metabolites produced by fungi, enter soils via various pathways. The contamination of soils with mycotoxins has been extensively documented, but their persistence remain uncertain. In a microcosm study, we investigated the adsorption–desorption behaviour and microbial transformation of four mycotoxins (LogK ow < −0.5) Deoxynivalenol (DON), Nivalenol (NIV), 15-Acetyl-Deoxynivalenol (15A-DON), and Zearalenone (ZEN, LogK ow = 3.83) in three agricultural soil types. We did not focus on the degradation potential of single species, but rather on the potential of soil microbiome as a whole. Mycotoxin adsorption varied depending on mycotoxin physicochemical properties and soil characteristics, with ZEN exhibiting the highest sorption affinity (> 88%), in contrast to DON and NIV (< 35% adsorption). Sorption of 15A-DON was significantly affected by the soil type (ranging from 21 to 97%), following the clay fraction, soil pH and to a lesser extent the organic matter content. The degradation of mycotoxins in all soils was found to be exclusively of microbial nature, with varying half-lives ranging from < 1 h for 15A-DON and up to 19 days for ZEN. The degradation was aligned with the soil microbial biomass (Cmic) and activity (respiration). The microbial O-deacetylation of 15A-DON to DON was confirmed in all investigated soils. Chemical modifications in the structure of mycotoxins resulted in more complex interactions with soil fractions affecting adsorption to soil i.e. 15A-DON and clay content. Independent of the mycotoxin, degradation was in line with the microbial activity of the soil ). These results highlight the pivotal role of soil characteristics in dictating mycotoxin mobility and stability, which is of paramount importance for environmental monitoring strategies and for ensuring agricultural safety and environmental contamination mitigation. Graphical Abstract